The Monetary Policy Shocks and Economic Growth: Evidence From SVAR Modelling - Musa, Ibrahim; Magaji, Sule; Salisu, Ali (International Journal of Indonesian Business Review, 2022)
ABSTRACT This study assesses the effect of monetary policy on economic growth in Nigeria. It used quarterly time series data from 1986Q1 to 2017Q4. SVAR analysis was used to assess the effects of monetary policy following the framework of Inflation Targeting (IT) on economic growth in Nigeria. Findings reveal that monetary policy has a positive shock on economic growth. The monetary policy rate (MPR) positively affects growth. Its effect was however minimal only accounting for a maximum of 3 percent. Also, the broad money supply (M2) had a positive shock but only accounting for a maximum of 7 percent. The study concludes that the inflation targeting (IT) framework is a good monetary policy tool but not sufficient. There is need for other supplementary instruments.